A bi-level model for optimal bidding of a multi-carrier technical virtual power plant in energy markets. (February 2021) - Foroughi, Mehdi; Pasban, Ali; Moeini-Aghtaie, Moein; Fayaz-Heidari, Amir
Highlights: Introducing a new framework for a TVPP in different energy markets. Examining the abilities of local heat markets in improving a TVPP's performance. Proposing the model in a multi-carrier energy environment. Extracting the optimization model as a bi-level problem. Abstract: Distributed energy resources (DERs) play an important role in the future vision of distribution energy networks. This paper with the aim of promoting DERs role in energy markets proposes a new framework for the optimal bidding strategy of a Technical Virtual Power Plant (TVPP) in different markets. In the proposed framework, it is assumed that the TVPP energy power is distributed throughout a multi-carrier energy network (MCEN) which consists of district heat networks (DHNs) and a distributed electricity network (DEN). In the MCEN, CHP units are the linkage between DHNs and DEN. With the goal of maximizing the profit of TVPP in different local and wholesale energy markets, a bi-level optimization model is formularized to set scheduling of DERs. As the upper level, the TVPP sets the schedule of its DERs considering technical constraints of DHNs and DENs. In the lower level, however, the TVPP runs an optimization problem to estimate the energy price in wholesale energy markets considering the forecasted bids of other rivals. The proposed model is implemented on a test system and the results confirms that the local market creates an opportunity for CHP owner, TVPP and the heat consumers to make more profit as well as achieving better technical performance for distribution energy systems.